2009
DOI: 10.1039/b820705d
|View full text |Cite
|
Sign up to set email alerts
|

Gd(iii) complex of a monophosphinate-bis(phosphonate) DOTA analogue with a high relaxivity; Lanthanide(iii) complexes for imaging and radiotherapy of calcified tissues

Abstract: A new phosphinic-acid DOTA-like ligand, DO3AP(BP), containing a geminal bis(phosphonic acid) moiety as a highly effective bone-seeking group, was synthesized in high yield. Its crystal structure was determined by X-ray analysis. Complexation with lanthanide(iii) ions occurs under mild conditions (pH = 8-9, 25 degrees C, 2-3 h). (1)H, (31)P, and (17)O NMR spectroscopy show that DO3AP(BP) forms nine-coordinated lanthanide(iii) complexes with one water molecule in the first coordination sphere except for Ln = Er-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 64 publications
4
41
0
Order By: Relevance
“…As we expected, some of the novel technetium-99m complex-conjugated Ogawa et al 6/35 bisphosphonate compounds showed superior biodistribution compared with previous compounds. This drug concept is applicable not only to technetium complex radiopharmaceuticals but also to other metals, such as rhenium [11][12][13][14][15][16][17][18], lutetium [19], yttrium [20], gadolinium [21], and so on. 68 Ga is one of the greatest practical and interesting radionuclides for clinical positron emission tomography (PET) because of its radiophysical properties (T 1/2 = 68 min) [22].…”
Section: Introductionmentioning
confidence: 99%
“…As we expected, some of the novel technetium-99m complex-conjugated Ogawa et al 6/35 bisphosphonate compounds showed superior biodistribution compared with previous compounds. This drug concept is applicable not only to technetium complex radiopharmaceuticals but also to other metals, such as rhenium [11][12][13][14][15][16][17][18], lutetium [19], yttrium [20], gadolinium [21], and so on. 68 Ga is one of the greatest practical and interesting radionuclides for clinical positron emission tomography (PET) because of its radiophysical properties (T 1/2 = 68 min) [22].…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] For the studied ligands, it has been shown that the lanthanide(III) ion is located inside the macrocyclic cavity binding to four nitrogen atoms of the ring and four carboxylate oxygen atoms, and there is no interaction with phosphonate/bis-(phosphonate) moieties in the side arm; the phosphorus(V) groups are freely available for interactions with other ions or substrates. [40,41,43,44] However, the amine and carboxylate groups are involved in the coordination, and, thus, they cannot interact with the sorbent. Nevertheless, the sorption of the carboxylate groups is very weak and could be considered negligible in comparison with phosphonates as it has been shown previously.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphonate/bis(phosphonate) group was used for anchoring the complexes on the surface of TiO 2 or other inorganic materials for application in magnetic resonance imaging (MRI). [40][41][42] In the complexes, the metal ion is bound in the macrocyclic cavity, whereas phosphonate groups are not involved in the coordination [43,44] and remain freely available for interaction with other metal ions or the particle surface. So, in contrast to most phosphonate/bis(phosphonate) complexes that have a direct coordination bond between the metal ion and the phosphonate groups, in this case, the metal complex is an "inert" component that does not influence the phosphonate sorption properties.…”
mentioning
confidence: 99%
“…Higher relaxivities can also be obtained by optimizing the hydration number and the residence time in the second sphere (q ss and τ mss ). For instance, the presence of phosphonates or phenolates which promotes hydrogen bond formation can increase relaxivity in dOTA and dTpA derivatives [25][26][27][28]. studies have shown the high contribution that can be achieved by the second sphere as molecules with q = 0 with optimized second sphere characteristics could even exhibit relaxivities close to q = 1 complexes [29,30].…”
Section: Complexation Chemistry Of Gadolinium: a Compromise Between Smentioning
confidence: 99%
“…Also, fullerenes incorporating three Gd 3+ ions have been tested for the visualization of brain tumor in rats after direct infusion into the brain. The very high relaxivity (in the range of 150-200 mM −1 s −1 at 2.4 T) produced good contrast with only 1/30 and 1/50 of the necessary dose for Gd 3+ -dTpA with Gd 3 n@C 80 -[dipeG5000(OH) n ] and Gd 3 n@C 80 (OH) 26 (CH 2 CH 2 COOM) 16 , respectively (M = H or na) [145,151].…”
Section: Gadofullerenesmentioning
confidence: 99%